1998
DOI: 10.1177/106907279800600302
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Review of Career Assessment Tools for Use With Diverse Individuals

Abstract: This paper briefly reviews the career-related issues facing employees with diverse surface characteristics (e.g., race/ethnicity, women, older workers, individuals with physical disabilities) and work status characteristics (e.g., part-time workers, contract employees, unemployed) at career choice and during career development. Following a description of these career issues, a review and evaluation of 44 psychometrically sound career assessment tools is provided that may be useful in individual assessment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…Although decidedness and related constructs of career decision-making have been well documented in the literature (e.g., Krieshok, 1998;Osipow, 1999;Osipow & Gati, 1998), its cultural relevancy is relatively unknown. Reviews of career assessment tools suggest that very little has been done to examine applicability of career assessment to the cultural minorities (Eby, Johnson, & Russell, 1998;Leong & Hartung, 2000;Leong & Leung, 1994). The failure to understand the impact of culture on the decision-making process and issues related to assessing culturally different individuals would result in inappropriate and invalid conclusions.…”
mentioning
confidence: 99%
“…Although decidedness and related constructs of career decision-making have been well documented in the literature (e.g., Krieshok, 1998;Osipow, 1999;Osipow & Gati, 1998), its cultural relevancy is relatively unknown. Reviews of career assessment tools suggest that very little has been done to examine applicability of career assessment to the cultural minorities (Eby, Johnson, & Russell, 1998;Leong & Hartung, 2000;Leong & Leung, 1994). The failure to understand the impact of culture on the decision-making process and issues related to assessing culturally different individuals would result in inappropriate and invalid conclusions.…”
mentioning
confidence: 99%
“…However, there has been research that recognized the racialized experiences of Black faculty within institutions of higher education (Davis et al, 2020; Jean-Marie et al, 2009), but “relatively little is known about Black professionals’ experiences of racial microaggressions at work” (Pitcan et al, 2018, p. 301). When Blacks are discussed in relation to career development outside of higher education, research is mainly focused on entry-level, low-skilled, and trade education (Eby et al, 1998; Watkins, 2013). As opposed to focusing on vocational training or physical labor, this research is beneficial because it includes the experience of knowledge workers, which are employees who sustain, produce, and improve a company’s strategies, resources, technology, and other functions to help corporations become more competitive and effective (Davenport, 2005).…”
Section: Race Matters: Race Racism and Workplace Incivility In Corpmentioning
confidence: 99%
“…Black women have encountered similar experiences of social isolation from White colleagues, including seclusion from White women (Hall et al, 2012). Studies have also indicated Black professional men and women are more likely to experience additional subjectivity and scrutiny of their work during the hiring and promotion process (Eby et al, 1998; Vallas, 2003), and they are less likely to have access to a high-ranking mentor who is willing to support their career development (Thomas, 2019). To overcome these challenges, DeSante (2013) explained there is a general philosophy that suggests “Blacks must work twice as hard as Whites to get half as far” (p. 342).…”
Section: Race Matters: Race Racism and Workplace Incivility In Corpmentioning
confidence: 99%
See 1 more Smart Citation
“…Although decidedness and related constructs of career decision making have been well documented in the literature [7,4], its cultural relevancy is relatively unknown. Reviews of career assessment tools suggest that very little has been done to examine applicability of career assessment to the cultural minorities [30,31,32].…”
Section: Literature Reviewmentioning
confidence: 99%